Emotional complexity Clarifying definitions and cultural correlates. [article]. - Grossman, Igor.
There is much debate about the notion of emotional complexity (EC). The debate concerns both the definition and the meaning of ostensible cultural differences in the construct. Some scholars have defined EC as the experience of positive and negative emotions together rather than as opposites, a phenomenon that seems more common in East Asia than North America. Others have defined EC as the experience of emotions in a differentiated manner, a definition that has yet to be explored cross-culturally. The present research explores the role of dialectical beliefs and interdependence in explaining cultural differences in EC according to both definitions. In Study 1, we examined the prevalence of mixed (positive-negative) emotions in English-language online texts from 10 countries varying in interdependence and dialecticism. In Studies 2-3, we examined reports of emotional experiences in 6 countries, comparing intraindividual associations between pleasant and unpleasant states, prevalence of mixed emotions, and emotional differentiation across and within-situations. Overall, interdependence accounted for more cross-cultural and individual variance in EC measures than did dialecticism. Moreover, emotional differentiation was associated with the experience of positive and negative emotions together rather than as opposites, but only when tested on the same level of analysis (i.e., within vs. across-situations). -- (from the authors)
Keywords: Culture; Emotional dialecticism; Emotional complexity; Emotional differentiation; Independence-interdependence.